Higher Volume Surgeons Have Lower Medicare Payments, Readmissions, and Mortality After THA. Issue 2 (February 2019) - Murphy, William S.; Cheng, Tony; Lin, Ben; Terry, David; Murphy, Stephen B.
Abstract: Background: The advent of value-based care, in which surgeons and hospitals accept more responsibility for clinical and financial results, has increased the focus on surgeon- and hospital-specific outcomes. However, methods to identify high-quality, low-cost surgeons are not well developed. Questions/purposes: (1) Is there an association between surgeon THA volume and 90-day Centers for Medicare & Medicaid Services (CMS) Part A payments, readmissions, or mortality? (2) What proportion of THAs in the United States is performed by low- and high-volume surgeons? Methods: We performed a retrospective analysis of the CMS Limited Data Set on all primary elective THAs performed in the United States (except Maryland) between January 2013 and June 2016 on patients insured by Medicare. This represented 409, 844 THAs totaling more than USD 7.7 billion in direct CMS expenditures. Surgeons were divided into five groups based on annualized volume of CMS elective THAs over the study period. Using linear and logistic regression, we calculated and compared 90-day CMS Part A payments, readmissions, and mortality among the groups. For each episode, demographic information (age, sex, and race), geographic location, and Elixhauser comorbidities were calculated to control for major confounding factors in the regression. Results: When compared with the highest volume group, each lower volume group had increased payments, increased readmission rates, and increased mortality rates in a stepwise fashion when controlling for patient-specific variables including Elixhauser comorbidity index, demographic information, region, and background trend. The lowest volume group resulted in 27.2% more CMS payments per case (p < 0.001; 95% confidence interval [CI], 26.6%–27.8%), had an increased readmission odds ratio (OR) of 1.8 (p < 0.001; 95% CI, 1.7–1.9), and an increased mortality OR of 4.7 (p < 0.001; 95% CI, 4.0–5.5) when compared with the highest volume group. There was also variation within volume groups: some lower volume surgeons had lower payments, readmissions, and mortality than some higher volume surgeons despite the general trend. In terms of CMS volume, surgeons who were at least moderate volume (11+ annual cases) performed 78% of THAs and represented 26% of operating surgeons. The low- and lowest volume surgeons (10 or fewer annual cases) performed only 22% of THAs in the United States while representing 74% of unique operating surgeons. Conclusions: There is a strong association between a surgeon's Medicare volume and lower CMS payments, readmissions, and mortality. Furthermore, the majority of Medicare THAs in the United States are performed by surgeons who perform > 10 CMS operations annually. Compared with previous work, these results suggest a trend toward higher volume surgeons in the Medicare population. The results also suggest a benefit to the shift toward higher volume surgeons in reducing payments, readmissions, and mortality for elective THA in the United States. However, given that payments, readmission, and mortality of surgeons varied widely, it is important to note that available individual CMS data can be used to directly evaluate each individual surgeon based on their actual results well as through association with volume. Level of Evidence: Level III, therapeutic study.